The South African Bill of Rights and the Development of Family Law - Bonthuys, Elsje (Juta Law, 2002)
Family law is probably the area of South African private law which has expanded and changed most rapidly in the past nine years. Many of these changes have come about as a result of the enactment of a Bill of Rights in both the interim and the final Constitution. 1 On the one hand, this is not surprising, since family law contains many legal rules which are overtly discriminatory on the bases of sex, gender, culture, religion and sexual orientation. On the other hand, legal rules in this area represent a codification of moral and social norms in the quotidian and 'private' lives of many people, which are often resistant to scrutiny and change.
Keywords: Family law; Bill of Rights; South African; Constitutional rights; Development; Common Law; Fundamental rights